The Development of Interactive Instructional Media Using Adobe Flash in a Form of Game on the Geometry Lesson (Cube and Cuboid) for Secondary School - Herdiansyah Herdiansyah; Yus Mochamad Cholily; Hendarto Cahyono (MEJ (Mathematics Education Journal), 2019)
The purpose of this study was developing an interactive instructional media using Adobe Flash in a form of the game at the geometry lesson (cube and cuboid) and analyzing the effectiveness of the media. The type of this study was Research and Development (R&D). The media development was started from potential and problem phase, data collection, product design, design validation, design revision, and product trial. The instruments of the study were the questionnaire validation and the questionnaire response of teacher and students. The results showed that development of interactive instructional media using Adobe Flash in a form of the game was valid. The average score of material expert was 3.43 and the average score of media expert was 3.61. The effectiveness of the media using Adobe Flash in a form of the game was effective. It was based on the score of teacher’s response was 78.57% and the score of students’ response was 86.42%.